Analisis Kompetensi Profesional Guru Dalam Meningkatkan Hasil Belajar Sosiologi - Mikael Bauk (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
The purpose of this study was to determine the professional competence of teachers in improving the learning outcomes of sociology in class X IPS 1 at Kapan State High School and the obstacles faced by Sociology teachers at Kapan Public High School in increasing their professionalism. This research uses a descriptive qualitative research method. Data collection techniques were carried out using observation, interviews, and documentation. The subjects of this study were the school principal and sociology teacher. The data analysis technique uses data reduction, compilation, categorization, and conclusions. Based on the results of this study show that teachers at Kapan State High School cannot be said to be professional; this is because, first, the learning process does not have a sociology subject teacher; some teachers are required to teach sociology even though the teacher is not a sociology subject teacher so that the delivery of sociology subjects is not according to the material presented by the teacher. Second, there are learning barriers that do not include the criteria for completeness of KKM in schools due to teachers who are not always in their scientific field in improving learning outcomes, such as teachers having difficulty in dividing teaching time between sociology and geography, lack of professional educators in the field of sociology, and lesson planning. Thus, the results of learning sociology at the Kapan State High School are ineffective. This is because schools still face many obstacles in providing educators who work in the field of sociology.